2014
DOI: 10.1111/evo.12500
|View full text |Cite
|
Sign up to set email alerts
|

Parent‐of‐origin growth effects and the evolution of hybrid inviability in dwarf hamsters

Abstract: Mammalian hybrids often show abnormal growth, indicating that developmental inviability may play an important role in mammalian speciation. Yet it is unclear if this recurrent phenotype reflects a common genetic basis. Here we describe extreme parent-of-origin dependent growth in hybrids from crosses between two species of dwarf hamsters, Phodopus campbelli and P. sungorus. One cross type resulted in massive placental and embryonic overgrowth, severe developmental defects, and maternal death. Embryos from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 101 publications
0
69
0
Order By: Relevance
“…However, it remains unclear if common forms of intrinsic hybrid sterility or inviability often reflect a common genetic basis that is regulatory in nature. Abnormal hybrid growth in mammals is broadly interesting in this context because it is a recurrent and rapidly evolving form of hybrid inviability for which there are strong a priori reasons to suspect a regulatory basis involving genomic imprinting (Brekke and Good ). In our study, we found a strong link between disrupted gene expression, genomic imprinting, and extreme hybrid overgrowth in dwarf hamsters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it remains unclear if common forms of intrinsic hybrid sterility or inviability often reflect a common genetic basis that is regulatory in nature. Abnormal hybrid growth in mammals is broadly interesting in this context because it is a recurrent and rapidly evolving form of hybrid inviability for which there are strong a priori reasons to suspect a regulatory basis involving genomic imprinting (Brekke and Good ). In our study, we found a strong link between disrupted gene expression, genomic imprinting, and extreme hybrid overgrowth in dwarf hamsters.…”
Section: Discussionmentioning
confidence: 99%
“…). Mammalian hybrids often show extreme parent‐of‐origin growth effects where reciprocal hybrids differ in size and are either much larger or smaller than the parental species (Vrana ; Brekke and Good ; Wolf et al. ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, biallelic expression of several genes, which contrasts with monoallelic expression of orthologous mouse genes, is observed in hybrids. For example, Grb10, Igr2r and Mash2, whose orthologous mouse genes are expressed maternally, show biallelic expression in the placentas of both reciprocal hybrids (Brekke and Good, 2014; Uno, Y., Ohishi, N., Tsuchiya, K., and Matsuda, Y., unpublished data). It is important to note that whether these genes undergo monoallelic or biallelic expression in parental species remains unclear.…”
Section: The Sterile Phenotype Of Phodopus Hybridsmentioning
confidence: 95%
“…Notably, parent-of-origin effects are observed in the growth phenotypes of embryos and placentas of the F 1 hybrids, which differ between the cross (P. campbelli females × P. sungorus males) and its reciprocal. In the cross between P. campbelli females and P. sungorus males, embryos and placentas grow normally, but in the reciprocal cross, embryos and placentas exhibit overgrowth (Brekke and Good, 2014; Uno, Y., Ohishi, N., Tsuchiya, K., and Matsuda, Y., unpublished data). The reciprocal cross leads to serious dystocia, which usually results in embryonic death before birth.…”
Section: The Sterile Phenotype Of Phodopus Hybridsmentioning
confidence: 98%